A retrospective review of aortic Stenosis in 274 dogs in Scotland : clinical presentation and diagnosis - Machado, Alice Cristina Victorino (Universidade de Lisboa, Faculdade de Medicina Veterinária, 2018)
Dissertação de Mestrado Integrado em Medicina Veterinária. In the dog, aortic stenosis (AS) is classified as a congenital heart defect; however, its nature is progressive and some authors believe it to be acquired. In reviews, it has been reported as the most common congenital cardiac defect in Europe. Anatomically, it is classified as sub-valvular, valvular or supra-valvular. Boxers, Newfoundland dogs, Golden Retrievers, German Shepherds, are among the breeds considered to be predisposed to some forms of this defect. The present retrospective review encompasses 274 dogs with aortic stenosis, examined and diagnosed by a mobile cardiology referral practice in Scotland in a period of 11 years. Diagnostic classification, signalment, clinical, electrocardiographic, and echocardiographic features were obtained from records. A statistical analysis was performed in order to characterize the sample and to assess relationships between variables. The majority of the dogs in the sample were Boxers (40.51%), followed by Golden Retrievers (12.77%), Labrador Retrievers (6.20%) and German Shepherd Dogs (4.74%). Contrarily to current information, the anatomical classification of AS in this study was mostly valvular (47.08%), followed by sub-valvular fixed lesions (30.66%). There were 40.51% dogs with clinical signs at presentation, the most frequent motive for consultation was a recently detected heart murmur (46.72%), and the most common clinical sign at presentation was intolerance to exercise (27.44%), followed by syncope (24.45%). There were slightly more males (56.57%) than females in the sample and a relationship between haemodynamic severity and gender was established, as males were more severely affected than females. The mean age at presentation was three years, and the age of dogs in the sample ranged from one month to 14 years of age. Although it is a congenital defect, its progressive nature could contribute to this age distribution. Most dogs had murmurs on auscultation and murmur intensity was associated with haemodynamic severity. The presence of echocardiographic findings, such as post-stenotic dilation (2.55%), concentric left ventricular hypertrophy (23.44%), aortic valve leaflet thickening (39.11%), and aortic regurgitation (63.14%) were related with severity. The presence of concurrent heart disease was common in the sample. Concomitant congenital defects found were pulmonic stenosis (4.74%), tricuspid valve dysplasia (17.42%) and mitral valve dysplasia (40.15%). Finally, we emphasize that a scientific consensus for diagnosis guidelines of aortic stenosis is much warranted. RESUMO - No cão, a estenose aórtica (EA) é classificada como um defeito cardíaco de origem congénita; contudo a sua natureza é progressiva e alguns autores consideram-na uma doença adquirida. Na Europa, é o defeito cardíaco congénito mais frequente. Quanto à localização anatómica das lesões, a EA é classificada como sub-valvular, valvular or supra-valvular. Cães das raças Boxer, Terranova, Golden Retriever e Pastor Alemão estão entre as que são consideradas como predispostas a alguns tipos espefícicos desta malformação. Este estudo retrospectivo incluiu 274 cães com estenose aórtica, examinados e diagnosticados por uma unidade móvel de referência em cardiologia na Escócia, durante um período de 11 anos. Variáveis como classificação em termos de diagnóstico, identificação do paciente, sinais clínicos, electrocardiográficos e ecocardigráficos foram obtidos a partir de relatórios. A análise estatística foi realizada com o fim de caracterizar a amostra e avaliar a relação entre variáveis. A maioria dos cães da amostra eram de raça Boxer (40.51%), Golden Retriever (12.77%), Labrador (6.20%) e Pastor Alemão (4.74%). Em contraste com dados de outros estudos, em termos de classificação anatómica de lesões, a EA valvular representou a maioria dos casos (47.08%), enquanto que a estenose subvalvular fixa apenas foi representada por 30.66% dos casos. Em termos da apresentação clínica, 40.51% dos cães apresentavam sinais, sendo que o mais frequente foi intolerância ao exercício (27.44%), seguido por síncope (24.45%). O estímulo iatrotrópico mais frequente foi a detecção de sopros em clínicas de primeira opinião (46.72%). A amostra apresenta um número ligeiramente maior de machos (56.57%) em relação a fêmeas, e uma relação entre o estadio da doença e o género foi estabelecida. A média da idade à apresentação foi de três anos, e neste contexto, a idade da amostra variou entre um mês e 14 anos. Embora se trate de um defeito congénito, a sua natureza progressiva pode justificar esta distribuição etária. A maioria dos cães apresentou um sopro à ausculatação, o qual foi relacionado com a estadio da doença. A presença de achados ecocardiográficos como a dilatação pós-estenótica (2.55%), hipertrofia concêntrica do ventrículo esquerdo (23.44%), espessamento dos folhetos valvulares da válvula aórtica (39.11%) e regurgitação aótica (63.14%) apresentaram também uma relação com o estadio da doença. A presença de doença concomintante na amostra foi frequente. A frequência de defeitos cardíacos congénitos associados na amostra por ordem crescente foi: estenose pulmonar (4.74%), displasia da válvula tricúspide (17.52%) e displasia da válvula mitral (40.15%). Por fim, enfatizamos que um novo consenso científico para directrizes de diagnóstico é relevante e necessário. N/A